Correlates Of Concept-Oriented And Socio-Oriented Family Communication In Two Malay Communities: A Comparative Study - Ismail, Narimah (1994)

(untitled)
Specifically the objectives of the study were to determine ( 1 ) the importance of parent - child communication; ( 2 ) the extent of parent - child communication pertaining to specific topics; ( 3 ) the practice of concept -oriented and sociooriented communication; ( 4 ) the agreement between mothers and children regarding concept - oriented and socio-oriented family communication style; ( 5) the problems related to parent - child communication; and (6 ) the relationships between concept - oriented and socio-oriented communication style with selected variables,including family income,educational level of mothers,family size,mothers' exposure to news and educational programmes on TV,mothers' values of conformity and self- directedness,degree of authoritarianism,information seeking behaviour of mothers,leadership status of mothers,and mothers' knowledge pertaining to parent - child communication.